Electrophilic fluorination of organosilanes. - Tredwell, M; Gouverneur, V (2006)
The fluorination of organosilanes with the silyl groups directly attached or adjacent to an aryl or alkenyl group has been only very recently examined despite the fact that the corresponding fluorinated products are synthetically useful building blocks. In these reactions, the silyl group enhances the reactivity of the pi-nucleophile and controls the sense of regiochemistry upon addition of the electrophilic source of fluorine. These reactions take advantage of the beta effect of the silicon-carbon bond and recent results from the literature revealed that this chemistry allows for the preparation of a variety of novel fluorinated building blocks including enantio-enriched derivatives.